Teaching Wh-Question To Young Learners Through Picture For Sekami Of Paroki Roh Kudus Tomohon - Tuilan, J (Journal of Educational Method and Technology, 2019)
This study intends to find out the effectiveness of using picture as teaching media in teaching WH-Question. The Subject consisted of 10 young aged students attending SEKAMI during the period November 2018 â€“ February 2019. The data were collected through objective test pre-experimental design of one group pre-test post-test. The data were analyzed based on descriptive statistics, in which the mean of pre-test was compared to the mean of post-test. The finding shows that students improved their achievement after being treated with picture. The mean of post-test is higher than the mean of pre-test (X2 is higher than that of X1 = 82.5 > 61.5). This indicates that the use of picture as a teaching media was interesting and made the students easy to understand the situation that had been explained to them.Â Keywords: WH-Question, Young learners, teaching through picture.